Secondary School Teachers ' Attitudes towards Provision of Sexual and Reproductive Health Education to Learners with Deafness in Tanzania - Sanga, Lwimiko Salum; Possi, Mwajabu K.; Ndabi, Joyce Sifa (Papers in Education and Development, 2022)
Abstract This study explored the attitudes of secondary school teachers towards provision of Sexual and Reproductive Health Education (SRHE) to secondary school learners with deafness in Tanzania. A small-scale survey design was used. Six regions and seven secondary schools with learners with deafness were purposively sampled. Similarly, 30 Biology and Civics teachers were purposively recruited for the study in which a questionnaire was used to gather data. The findings indicated that teachers had a negative attitude towards the provision of SRHE with the mean score of 37.83. Additionally, Kruskal €“Wallis Test showed no statistical difference on age (p = .252), sex (p = .778), teaching experience (p = .67), levels of education (p = .185) and religion (p = .884). The study concludes that the attitude of teachers towards teaching SRHE to learners with deafness was negative due to lack of training on deafness and SRHE. The study recommends to the government and relevant institutions to provide both pre €“ and in-service training on sexuality issues in secondary schools. Keywords: attitude, deafness, education, reproductive health, sexuality